Emerging New Concepts of Degrader Technologies. (July 2020) - Ding, Yu; Fei, Yiyan; Lu, Boxun
Abstract : Traditional drug discovery focuses on identifying direct inhibitors of target proteins. This typically relies on a measurable biochemical readout and accessible binding sites whose occupancy influences the function of the target protein. These requirements preclude many disease-causing proteins from being 'druggable' targets, and these proteins are categorized as 'undruggable'. The proteolysis-targeting chimera (PROTAC) technology provides powerful tools to degrade these undruggable targets and has become a promising approach for drug discovery. However, the PROTAC technology has some limitations, and emerging new degrader technologies may greatly broaden the spectrum of targets that could be selectively degraded by harnessing a second major degradation pathway in cells. We review key emerging technologies that exploit the lysosomal degradation pathway and discuss their potential applications and limitations. Highlights: Selective degradation of pathogenic proteins is a promising strategy to drug 'undruggable' targets. Established degrader technologies such as PROTAC are extremely promising but still have limitations. The lysosome is a major degradation pathway utilized by cells to degrade extracellular and intracellular content. New technologies such as LYTAC, AUTAC, and ATTEC may have potential applications in several diseases by exploiting the lysosome for targeted degradation.